2003
DOI: 10.1002/aoc.439
|View full text |Cite
|
Sign up to set email alerts
|

Syndiotactic polymerization of styrene catalyzed by alkenyl‐substituted cyclopentadienyltitanium trichlorides

Abstract: (3) have been synthesized and characterized. The influence of the alkenyl substituent groups on the catalyst activities in the syndiotactic polymerization of styrene was investigated. The catalyst activities decreased in the order CH 2 CHCH 2 CH 2 CpTiCl 3 > CH 3 CH 2 CH 2 CH 2 CpTiCl 3 > CH 3 CH 2 CH 2 CpTiCl 3 > CH 2 CHCH 2 CpTiCl 3 (Cp C 5 H 4 ). By using complex 1, the dependence of the activity on the concentration of methylaluminoxane, triisobutylaluminum and diisobutylaluminum hydride was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…BF 3 Á OEt 2 was Table 4 Syndiotactic polymerization of styrene in bulk catalyzed by RCpTi(OMe) 3 distilled from CaH 2 at reduced pressure before use. CpTi(OMe) 3 [37], i PrCpTiCl 3 [38], Me 3 SiCpTiCl 3 [39], CH 2 @CHCH 2 CpTiCl 3 [40], and PhCH 2 CpTiCl 3 [41] were synthesized by using published methods. The general procedure for the preparation of RCpTi(OMe) 3 was carried out as in the literature [41].…”
Section: Methodsmentioning
confidence: 99%
“…BF 3 Á OEt 2 was Table 4 Syndiotactic polymerization of styrene in bulk catalyzed by RCpTi(OMe) 3 distilled from CaH 2 at reduced pressure before use. CpTi(OMe) 3 [37], i PrCpTiCl 3 [38], Me 3 SiCpTiCl 3 [39], CH 2 @CHCH 2 CpTiCl 3 [40], and PhCH 2 CpTiCl 3 [41] were synthesized by using published methods. The general procedure for the preparation of RCpTi(OMe) 3 was carried out as in the literature [41].…”
Section: Methodsmentioning
confidence: 99%
“…[23] Deuterated solvents and dme were dried by distillation from the appropriate drying reagents. The following instruments were used for physical characterization of the com- [24] LiA C H T U N G T R E N N U N G [(C 5 H 4 )PtBu 2 ], [12] (SiMe 3 )C 5 H 4 (CH 2 CH= CH 2 ), [25] BA C H T U N G T R E N N U N G (C 6 F 5 ) 3 , [16c, 26] and HBA C H T U N G T R E N N U N G (C 6 F 5 ) 2 . [14] X-ray Crystal-Structure Analysis Data sets (from Münster) were collected with Nonius Kappa CCD diffractometers; Mo radiation equipped with a rotating anode generator.…”
Section: General Proceduresmentioning
confidence: 99%
“…In general, the introduction of bulky substituents in the Cp ring reduced the catalytic activity. It was believed that the coordination and insertion of the monomer may not have been affected by the misalignment of the butenyl group with the active center or weak coordination of the butenyl double bond [50].…”
Section: Mono-cp' Titanocene Catalystsmentioning
confidence: 99%
“…Qian et al reported mono-alkoxy-substituted mono-indenyl titanocene complexes, IndTiCl 2 (OR) (R = Me, Et, Pr, Cy = cyclohexyl) (39-42) (Figure 3). Substitution of Cl atoms with one single alkoxy group could enhance the catalytic activity of the mono-Cp' titanocenes [49,50,52]. For the mono-indenyl titanocene complexes, the catalytic activity could also be improved to a considerable magnitude by introducing a σ-coordinated ancillary alkoxy ligand.…”
Section: Mono-cp'-re Metal Catalystsmentioning
confidence: 99%